Study of charmonium and charmonium-like contributions in B+ → J/ψηK+ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2022)
A study of B+ → J/ψηK+ decays, followed by J/ψ → μ+μ− and η → γγ, is performed using a dataset collected with the LHCb detector in proton-proton collisions at centre-of-mass energies of 7, 8 and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The J/ψη mass spectrum is investigated for contributions from charmonia and charmonium-like states. Evidence is found for the B+ → (ψ2(3823) → J/ψη)K+ and B+ → (ψ(4040) → J/ψη)K+ decays with significance of 3.4 and 4.7 standard deviations, respectively. This constitutes the first evidence for the ψ2(3823) → J/ψη decay.